Association between polymorphisms of cytokine genes and brucellosis: A comprehensive systematic review and meta-analysis. (March 2020) - Zafari, Parisa; Zarifian, Ahmadreza; Alizadeh-Navaei, Reza; Taghadosi, Mahdi; Rafiei, Alireza
Highlights: Cytokine gene polymorphisms are involved in brucellosis risk. rs2243250 and 1946519 have a positive correlation with brucellosis. rs1800470, 1800471, 1800629, 1800872 and UTR5644 are protective factors in brucellosis. Abstract: Objective: Owing to involvement of host genetic factors in susceptibility to brucellosis infection and its outcome, this study aimed to carry out a comprehensive systematic review and meta-analysis to derive a precise evaluation of the association between the risk of brucellosis and its focal complication and all cytokines examined in case-control studies, including Interferon gamma (IFN-γ), Tumor Necrosis Factor (TNF)-α, TNF-β, Transforming Growth Factor (TGF)-β, IL-2, IL-4, IL-6, IL-10, IL-12B, IL-15, and IL-18 polymorphisms. Methods: A systematic literature search in PubMed, Web of Science, Google Scholar, and Scopus was performed to identify the relevant studies, and related information was extracted. The effect size (ES) and corresponding 95% confidence intervals (CIs) were calculated to estimate the association. Results: From 158 initial results, twenty-five eligible studies were included in the meta-analysis. Overall, the pooled results showed that the dominant models of IFN-γ UTR5644, TGF-β rs1800470 and rs1800471, TNF-α rs1800629, and IL-10 rs1800872 were significantly less frequent in brucellosis patients than the controls. Also, the pooled analysis of the mutant allele vs. wild allele of TGF-β rs1800471 and IL-10 rs1800872 showed negative association with brucellosis risk. On the other hand, our pooled analysis demonstrated that the mutant allele of IL-4 rs2243250 and IL-18 rs1946519 were associated with increased susceptibility to brucellosis. In addition, the IFN-γ UTR5644 and TGF-β rs1800470 were more frequent in the patients without focal forms. Conclusions: IL-4 rs2243250 and IL-18 rs1946519 have a positive correlation with brucellosis whereas the IFN-γ UTR5644, TGF-β rs1800470 and rs1800471, TNF-α rs1800629, and IL-10 rs1800872 showed a negative association with this disease. The association between the other single nucleotide polymorphisms (SNP) and brucellosis risk was not confirmed in the current meta-analysis. PROSPERO Registration: CRD42018117203.